"Broken-hearted" carbon bowl via electron shuttle reaction: energetics and electron coupling. Issue 19 (13th April 2021) - Leith, Gabrielle A.; Rice, Allison M.; Yarbrough, Brandon J.; Kittikhunnatham, Preecha; Mathur, Abhijai; Morris, Nicholas A.; Francis, Megan J.; Berseneva, Anna A.; Dhull, Poonam; Adams, Richard D.; Bobo, M. Victoria; Vannucci, Aaron A.; et al.
Abstract : An electron shuttle contributed to breaking corannulene's heart through a unique one-step reductive CC bond cleavage in the traditionally robust π-bowl. The heartbreak did not stop there as "broken analogs" were developed through a solution-phase route. Abstract : Unprecedented one-step CC bond cleavage leading to opening of the buckybowl (π-bowl), that could provide access to carbon-rich structures with previously inaccessible topologies, is reported; highlighting the possibility to implement drastically different synthetic routes to π-bowls in contrast to conventional ones applied for polycyclic aromatic hydrocarbons. Through theoretical modeling, we evaluated the mechanistic pathways feasible for π-bowl planarization and factors that could affect such a transformation including strain and released energies. Through employment of Marcus theory, optical spectroscopy, and crystallographic analysis, we estimated the possibility of charge transfer and electron coupling between "open" corannulene and a strong electron acceptor such as 7, 7, 8, 8-tetracyanoquinodimethane. Alternative to a one-pot solid-state corannulene "unzipping" route, we reported a nine-step solution-based approach for preparation of novel planar "open" corannulene-based derivatives in which electronic structures and photophysical profiles were estimated through the energies and isosurfaces of the frontier natural transition orbitals.